The Use of Populism as a Pragmatist Approach in Indonesia - Albert Triwibowo; Jessica Martha (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2021)
Populism usually appears when there is dissatisfaction towards the system, and creates two different camps seen as polarization, “the elite” versus “the people.” Those camps are a result of the appeal of anti-elite. Indonesian populist leader also uses the strategy to appeal a large support of citizens, but the strategy must be understood as a part of pragmatist leadership. This paper argues that the utilization of populism in Indonesia is more motivated by pragmatic reasons rather than fundamental reasons. This pragmatic reason can be seen through inconsistent statement in the leadership which, at first, supports populist claim but tends to be different in reality. Political leaders in Indonesia try to strive for a progress as well as to seek a compromise and a support from various groups, including those labeled as elite by the populists themselves. Through an observation of secondary documents from journals and news articles during the latest presidential campaign between Jokowi and Prabowo in 2019, it is concluded that all characteristics of populist strategy have been used pragmatically by both leaders. It is applied to attract more supports in order to respect the political constraints and to work with the system.